Modernization of Indonesian Naval Fleet to Realize Asta Cita - Setiawati, Deni; Soemantri, Asep Iwa; Legowo, Endro; Prakoso, Lukman Yudho; Risahdi, Muhamad (CV. Publikasi Indonesia, 2025)
This research discusses the modernization of Indonesia's naval fleet as a strategic effort to realize Asta Cita, which is the ideal of the Indonesian nation in maintaining maritime sovereignty, improving maritime security, and strengthening the role of the state in the regional region. The research method used is descriptive qualitative with analysis of documents, literature, and secondary data from relevant government agencies. The results show that the modernization of the naval fleet, including the procurement of advanced patrol vessels, warships, and cutting-edge surveillance technologies, is able to improve the effectiveness of maritime defense, hybrid threat mitigation, and support for maritime resource management. This modernization is the key to achieving Asta Cita in a sustainable manner.